Max Weber diante do Socialismo - Carvalho, Davi Gustavo de [UNESP] (2008)
This work aims to analyse Max Weber's perspective in relation to the socialism. This great classic of the social thought argued against the feasibility of the socialist project from a very critical point of view. More precisely, this work delineates and analyses the double biased Weberian criticism towards socialism: Weber not only opposes the idea that the human emancipation would be reached in an established socialist society, but also criticises the possibilities of success of a social revolution that could lead to that sort of society. Unveiled the arguments that underpin Weber's criticism, the subsequent critical discussion of the author's reasons is addressed in the light of the historical background in which the German thinker has come up with them. The chain of values that guided the author, which provides the basis for his political-ideological position, seems to exert great influence on the view he holds on socialism, which he has only seen as an extensive form of the bureaucratic domination, something that has already existed in its predecessor, the modern capitalism. Taking that very idea as pivotal, that negative view of socialism, Weber has considered there was no way out for the cage of iron of bureaucracy, thus claiming it was something inexorable in modern times, either in capitalism or in socialism, capitalism's supposed antipodal. Finally, even though some historical developments of the socialist experiences give reason to Weber's arguing, the Weberian theorisation and his arguing, whose strength and influence are undeniable, are questioned here based on some critical elements. In order to do so, a wide range of Weber's works are browsed and analysed; the famous Conference on Socialism, though, proffered by Weber in 1918, is here taken as the fundamental document for research